2006
DOI: 10.1042/cs20060144
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac mitochondrial cGMP stimulates cytochrome c release

Abstract: Although the existence of cardiac mitochondrial cGMP has been reported previously [Kimura and Murad (1974) J. Biol. Chem. 249, 6910-6916], the physiological and pathophysiological properties of cGMP in cardiac mitochondria have remained unknown. The aim of the present study was to clarify whether cardiac mitochondrial cGMP regulates the apoptosis of cardiomyocytes. In the presence of GTP, the NO donors SNAP (S-nitroso-N-acetyl-DL-penicillamine; 1 mmol/l) and SNP (sodium nitroprusside; 1 mmol/l) each markedly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…The NO/GC/cGMP pathway is also involved in cell survival [32,35]. Previous studies have associated NO in apoptosis with the formation of highly reactive oxidants, such as peroxynitrite (ONOO-) or hydroxyl peroxide [26,30].…”
Section: Introductionmentioning
confidence: 99%
“…The NO/GC/cGMP pathway is also involved in cell survival [32,35]. Previous studies have associated NO in apoptosis with the formation of highly reactive oxidants, such as peroxynitrite (ONOO-) or hydroxyl peroxide [26,30].…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that NO donors, to increase mitochondrial cGMP concentration, induce cytochrome c release from mitochondria, followed by cardiomyocyte apoptosis; we also showed that 1H- [1,2,4]oxadiazolo [4,3-a]quinoxalin-1-one (ODQ), an NO-sensitive guanylyl cyclase inhibitor, inhibits cardiomyocyte apoptosis under ischemia-reperfusion conditions (Seya et al, 2007). However, NO and cGMP do not induce mitochondrial swelling or membrane depolarization.…”
Section: Introductionmentioning
confidence: 95%
“…The adequacy of anesthesia was monitored from the disappearance of righting reflex or pedal withdrawal reflex. Each heart was isolated, the aorta was cannulated under artificial respiration, and both were quickly removed as a unit and hung on a Langendorff-type apparatus to start the coronary perfusion with a Ca Rat cardiac mitochondria were prepared as described previously (Seya et al, 2007). Briefly, heparinized adult Wistar rats (n 5 23, 350-400 g) were anesthetized with pentobarbital sodium (50 mg/kg i.p.).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations